Preparation of reduced graphene oxide-based working electrode and counter electrode for dye-sensitized solar cell application - Jumeri, Nor Fathin Aini (2015)
In this work, the enhancement of dye-sensitized solar cell (DSSC) using graphene-based materials for the making of working and counter electrodes was explored. Titanium dioxide (TiO2) film was deposited on an indium tin oxide (ITO) glass by an in-house aerosol-assisted chemical vapour deposition method (AACVD). Graphene oxide (GO) was then introduced onto the TiO2-ITO substrate by dip-coating and the layer of GO was successively thermally treated to reduced graphene oxide (rGO). The TiO2-rGO film was used as a compact layer for the working electrode of the DSSC, which served as a blocking layer where it prevented the undesired back electron transfer and increased the photoconversion efficiency of DSSC. Compact layer was introduced in this work to overcome the issue of electrons recombination which caused the photocurrent loss and seriously decrease the photovoltaic performance of DSSC. A layer of zinc oxide-silver (ZnO-Ag) was introduced atop the compact layer as an active material by a dr. blade approach. The ZnO-Ag was synthesized using a microwave method and composed of a highly porous flower-shaped morphology, which was advantageous for adsorption of dye. An in-situ electrochemical polymerization method for the fabrication of polypyrrole nanoparticles incorporated reduced graphene oxide and ptoluenesulfonate (pTS) (Ppy-rGO-pTS) on a conducting ITO glass was used as a counter electrode for the platinum (Pt)-free DSSC since Pt material is one of the most expensive materials in DSSC. In addition, Ppy-rGO-pTS merits in excellent electron conductivity and high electrocatalytic activities. Cyclic voltrammetry (CV) was employed to determine the solar conversion efficiency. The efficiency of the ZnO-Ag-TiO2 photoanode in this work was far lower than the photoanode of ZnO-Ag-TiO2-rGO owing to the presence of rGO,which enhanced the electrochemical performance. The DSSC assembled with the Ppy-rGO-1.0pTS counter electrode exhibited an enhanced power conversion efficiency of 1.99% under the solar illumination, as compared to using conventional Pt as a counter electrode (0.08%), which was attributed to the increased contact area between Ppy-rGO-pTS counter electrode and electrolyte, which also subsequently improved the conductivity of the Ppy-rGOpTS counter electrode. The objectives of this work are to investigate the photocurrent performance of a working electrode, which composed of a titanium dioxide-reduced grapheme oxide (TiO2-rGO) compact layer produced via aerosol assisted chemical deposition (AACVD) and dip-coating methods,and a zinc oxide-silver (ZnO-Ag) active layer produced via a microwave method, to assess the performance of a polypyrrole-reduced graphene oxide-ptoluenesulfonate (Ppy-rGO-pTS) counter electrode for a Pt-free DSSC and to study the efficiency of photovoltaic performance for ZnO-Ag-TiO2-rGO as a working electrode and Ppy-rGO-pTS as a counter electrode. The as-fabricated DSSC exhibited novelty in terms of using Ppy-rGO-1.0pTS counter electrode as a promising alternative counter electrode for low-cost and high-efficiency DSSCs, and making use of rGO as an active material to enhance solar conversion.